How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694602 ZenodoArchiveConcept: 10694601 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080734 10.53832/edtechhub.1015
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

How Can Decision-Makers Assess EdTech Interventions for Cost-Effectiveness to Enable Better Investments? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how decision-makers should consider cost-effectiveness when contemplating investing in EdTech programmes. Cost-effectiveness is a critically important consideration for anyone planning investments in EdTech, but it is also a complex one, which requires understanding the total cost of an intervention and comparing it against the likely impact on education. We draw on work from EdTech Hub and other prominent researchers to distil key practical insights for decision-makers on how to apply cost-effectiveness analysis to their decision-making. Practical considerations include recommendations on gathering the right data for analysis; ensuring cost calculations are holistic; leveraging existing frameworks and tools for cost and impact calculations; and ensuring that comparisons are made against non-tech interventions as well as the broader resource envelope available for education to determine affordability in a given context. Finally, we explore areas where additional work is needed, including an increased understanding of the challenges faced by decision-makers in considering cost-effectiveness and the need for greater transparency and accountability in cost-effectiveness analysis in the sector. Keywords Cost-effectiveness; EdTech; education policy; total cost of implementation; affordability; Learning-Adjusted Years of Schooling An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10837295 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1018 ZenodoArchiveConcept: 10837294
Keywords: _r:AddedByMyEducationEvidence

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14727493 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1088 ZenodoArchiveConcept: 14727492
Keywords: _r:AddedByMyEducationEvidence

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10604329 ZenodoArchiveConcept: 10604328 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080685 10.53832/edtechhub.1005 2405685:GXMUGXHE 2405685:RK44C9BZ
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence